Identification of Re-Interpreting Traditional Javanese Architecture for Design Concepts of Balai RW 7 Dusun Genting, Kelurahan Merjosari, Malang City - Hamka; Suryo Tri Harjanto; Adhi Widyarthara (Architectural Research Journal, 2021)
The identification of traditional architectural elements in the design plan of Balai RW 7 tries to apply a study of reinterpretation of traditional architecture in order, to know the architectural elements that can be applied to the design concept. The purpose of this study is to find architectural elements of Javanese houses that can be used as the basis for transformation in the contemporary design of Balai RW 7. This study was written using a qualitative descriptive analysis method to analyze data compiled from literature sources in national journals that discuss elements of traditional Javanese architecture. The elements of traditional Javanese architecture are then reinterpreted descriptively based on the functions and facilities contained in the Balai RW plan. The results found elements of Javanese architecture that could be applied to the design concept, namely the display focused on the transformation of the 5 typologies of the roof of the Javanese house, the spatial pattern adapted to the functions and facilities of the Balai RW, the transformation of ornamentation of flora, fauna, nature, and belief, the orientation is directed to face north or south but still adapts to the existing conditions of the site and the environment, some materials use more modern substitute materials, as well as the transformation of the roof construction of empyak raguman and the construction of umpak, soko guru and tumpang sari in the receiving area with materials using several substitute materials.